Relación entre el síndrome de Burnout y la calidad de vida del profesional de enfermería de la Clínica Good Hope, julio 2009 - Sotelo Rosales, Marisol (2019)
Objective: To determine the relationship that exists between the Burnout Syndrome and the Quality of Life in nursesfrom the “Good Hope” Clinic. Methodology: A transversal correlational study was performed. The selected universe was composed of 35 nurses from the “Good Hope” Clinic in July of 2009. The Maslach Burnout Inventory Questionnaire was used to measure burnout syndrome, and the SF-36 Medical Outcomes Study was used for the qualityof life. The data were processed using the SPSS v.15 statistical package through which the tests of hypotheses wereperformed for the chi-square with 95% confidence level. Results: As results, according to Maslach Questionnaire,which was obtained from all the surveys, it was found that the average in the area of emotional burnout was 26indicating a medium level; in the same way in the area of depersonalization it was obtained an average of 10 whichindicates a media depersonalization level. On the other hand in the area of personal accomplishment it was obtainedan average of 49 which indicates a low level. With respect to the 8 dimensions of quality of life: physical functionhas a maximum score of 92, then with 88 for physical role, and 80 for emotional role. The lower scores correspondto poor quality of life, these are: general health, vitality average of 66 and 70 for bodily pain. The Pearson R testindicated that emotional burnout was significantly related to physical function (P = 0.003 <0.05), bodily pain (P = 0.048 <0.05), general health (0.013 <0.05), vitality (P = 0.003 <0.05), social function (P = 0.041 <0.05) and mentalhealth (P = 0.002 <0.05), on the other hand we can observe significant relationship in the personal accomplishmentwith physical function ( P = 0.004 <0.05), vitality (P = 0.013 <0.05) and mental health (P = 0.013 <0.05). Conclusions: Nurses from the “Good Hope” Clinic have better quality of life in physical function, physical role, andemotional role. These nurses also have an average mean level of emotional burnout and depersonalization and lowlevels of depersonalization. It should be noted that nurses are in tendency to develop this syndrome; therefore wesuggest carrying out preventive programs that meet the specific needs of the institution to maintain a high degree ofsatisfaction of nurses and patients.